Pecinan Tambak Bayan Surabaya Dalam Fotografi Dokumenter - Alfian Rizal Andre Ciputra; Pitri Ermawati; Syaifudin Syaifudin (Specta: Journal of Photography, Arts, and Media, 2019)
Documentary Photography of Chinatown in Tambak Bayan Surabaya. Chinese etchnic of Surabaya has been living in the settlement, called Tambak Bayan Surabaya, around Kalimas River. Most of the families living there are the third and fourth generation of the Chinese ethnic whom  migrated to Surabaya several years ago. Those families occupied the buildings formerly were horse stables during colonial period. Their economic condition was classified as middle to lower class. Hence,  they did not have other choices but those settlements. Documentary photography is a way to describe their everyday conditions in a 4x4 quadrangle house that is high. Chinese identities that surround their homes are each the size of each family inhabiting the house. The families residing in Chinatown Tambak Bayan Surabaya can be visualized into several documentary photographic works showing their condition and their dwelling places.  Keywords: documentary photography, Chinatown’s Tambak Bayan Surabaya, Chinese New year